GPS and ApRES data relating to the growth of Chasm-1, Brunt Ice Shelf from 2016 to 2023 ... - Marsh, Oliver; De Rydt, Jan (NERC EDS UK Polar Data Centre, 2025)
The dataset consists of GPS data recorded from four sites close to Halley VI Research Station, plus ApRES data across the rift from 2017-2019. Both data types provide information on the width of an active rift propagating through the ice shelf. GPS sites advect with flow of the ice shelf, while ApRES is repositioned each year. The data were collected as part of the Lifetime-of-Halley monitoring programme. This work was funded by NERC grant NE/X014991/1 (RIFT-TIP) and supported by NERC Antarctic Logistics and Infrastructure. ... : The GPS sites were installed between 2016 and 2017 and recorded for 2 hours 15 minutes each day at 30 second resolution. Data was converted from raw Leica format (*.m00) to standard Rinex v2 format using UNAVCO's teqc.exe program. The ApRES was installed in a horizontal configuration with antennas spaced approximately 15 m apart. A metal reflector was installed on the far side of the crack and the peak in reflection indicates the distance across the crack. The ApRES raw DAT format was converted to ApRES raw netCDF format using the bas-apres software (v0.3.0). Details in Marsh et al., 2024. ...